Ethical and methodological challenges in the research on teachers’ literacy -Opening new paths - De Grande, Paula Baracat; Valsechi, Marília Curado; Vianna, Carolina Assis Dias (Íkala, Revista de Lenguaje y Cultura, 2019)
We aim in this essay to discuss the ethical and methodological challenges in research works in the domain of literacy studies, within the field of applied lin-guistics. To do this, we will rely upon research design carried out in the group Letramento do Professor (Teachers’ literacy). Focused in the ethical approach of research work, the field of Literacy studies has been oriented for over two decades towards understanding and acting in settings in which writing (re)establish the strains and conflicts that have, for a long time, historically mar-ginalized large segments of Latin American populations. In the discussion on ethical aspects of research on literacy and teacher training, we highlight the im-portance of drawing attention to power relations in unequal settings in order to foster confidence among minority or subalternized social groups, such as pre-service teachers, thus rethinking the role of researcher as he or she chooses to study such groups.